2019
DOI: 10.21470/1678-9741-2019-0067
|View full text |Cite
|
Sign up to set email alerts
|

Syntax Score I and II for Predicting Carotid Artery Stenosis in Patients with Multivessel Coronary Artery Disease: A Propensity Score Matching Analysis

Abstract: ObjectiveTo evaluate the predictive accuracy of SYNTAX score (SS) I and II for detecting significant carotid artery stenosis (CAS) in patients with multivessel coronary artery disease undergoing coronary artery bypass grafting (CABG) surgery.MethodsThe study population consisted of 416 patients. Clinical, demographic, and radiological records were retrospectively reviewed. Characteristics of patients with CAS (n=66) and patients without CAS (n=350) were compared before and after propensity score matching analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…A similar correlation between the intima-media thickness of the carotid artery and Syntax score I and II was reported by the teams of Saedi et al, Ikeda et al, Aksu et al, and Korkmaz et al [27], [28], [29], [30]. The results of Ozturk and Sahin and Costanzo et al and col [31], [32], [33] are opposing. Despite the various incidences cited above, the combination of carotid and coronary atherosclerosis is an indisputable clinical fact.…”
Section: Discussionsupporting
confidence: 76%
“…A similar correlation between the intima-media thickness of the carotid artery and Syntax score I and II was reported by the teams of Saedi et al, Ikeda et al, Aksu et al, and Korkmaz et al [27], [28], [29], [30]. The results of Ozturk and Sahin and Costanzo et al and col [31], [32], [33] are opposing. Despite the various incidences cited above, the combination of carotid and coronary atherosclerosis is an indisputable clinical fact.…”
Section: Discussionsupporting
confidence: 76%
“…SYNTAX score is widely used by interventional cardiologists and cardiothoracic surgeons to predict the severity/complexity of coronary artery disease and to determine the post-operative outcome of patients undergoing CABG or PCI. Literature from international centers shows favorable outcome of CABG if the Syntax score comes more than ≥34 [18][19][20]. In our study only 7.2% (n = 11) patients had Syntax score more than 34 and fall into high-risk Syntax score group while the majority had low (75.2%, n 115) and intermediate (17.6%, n = 27) risk Syntax score, respectively and when high-risk Syntax score patients were separately evaluated for correlation with HbA1c levels, we have observed an insignificant association.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of CAS has been shown to be a significant risk factor for peri-post-operative stroke in patients undergoing CABG, with a prevalence of 3% in unilateral stenosis, 5% in bilateral stenosis, and 7% in total carotid occlusion. [10,31,32] Therefore, screening for CAS before CABG in patients with intermediate and high SS may be reasonable. In conclusion, we demonstrated that there was a proportional increase in the severity of CAS to CAD complexity using SS.…”
Section: Discussionmentioning
confidence: 99%